An Investigation of Revaluations of Tangible Long-Lived Assets - Easton, Peter D.; Eddey, Peter H.; Harris, Trevor S. (Journal of Accounting Research, 1993)
Peter D. Easton, Peter H. Eddey, Trevor S. Harris, An Investigation of Revaluations of Tangible Long-Lived Assets, Journal of Accounting Research, Vol. 31, Studies on International Accounting (1993), pp. 1-38